Determinan Biaya Modal: Studi Pada Perusahaan Non-Keuangan - Nanik Lestari; H. Hidayatullah (Esensi: Jurnal Bisnis dan Manajemen, 2018)
The cost of equity capital represents the number of expenses that must incur or must be paid to obtain capital either from debt, stock preference, ordinary shares, or retained earnings to finance corporate investment. This study aimed to examine the effect of voluntary disclosure, leverage and the market value of equity on the cost of equity capital. Samples in this research were 314 companies in the non-financial sector and were selected using purposive sampling method. The measurement used for the independent variables are voluntary disclosure, leverage, and market value of equity and dependent variable used cost of equity. Measures for control variable in this research is firm size. The results showed that only voluntary disclosure variables that significantly affect the value of equity capital, while the other two variables are not significant.DOI: 10.15408/ess.v8i2.7597